Genetic and environmental factors shaping goat milk oligosaccharide composition - R Gonzalez-Prendes; R.P.M.A. Crooijmans; B. Dibbits; K. Laport; S. Breunig; P. Keijzer; L. Pellis; H. Bovenhuis (Journal of Dairy Science)
ABSTRACT: Oligosaccharides (OS) in milk have been suggested to influence the health and development of the newborn by promoting growth of beneficial gut bacteria, stimulating brain development, and enhancing immune functions. Goat milk is a natural source of specific OS, which could be a potential beneficial ingredient for infant formula. In this study, goat milk OS (gMOS) content from ∼1,000 dairy goats across 18 commercial farms was studied. A genomic relationship matrix was used to unravel genetic and environmental factors shaping gMOS content. The most abundant gMOS identified was 3′-N-glycolyl-neuraminyl-lactose (NGL), with a concentration of 32.05 mg/kg, whereas 3-fucosyllactose (FL) exhibited the lowest concentration at 1.85 mg/kg. Acidic OS had a notably higher content (81.67 mg/kg) than neutral OS (24.88 mg/kg). High variability in gMOS content was observed among individual goats, which could for a large extent be attributed to genetic differences. Heritability estimates ranged from 31% for 3′-galactosyllactose (GL) to 85% for 3-FL. High positive genetic correlations (>0.57) were estimated between 3′-sialyllactose (SL) and 6′-SL, and between 6′-GL and 3′-GL. The contribution of differences between farms to variation in milk OS content varied from 3% for 3′-NGL to 45% for 6′-SL. Although gMOS such as 3′-GL, 6′-GL, and 6′-NGL, were significantly influenced by systematic environmental factors such as the lactation stage, the effect of these factors was relatively minor compared with the importance of genetic and farm effects. This research, which stands out due to its relatively large sample size, underscores the pivotal role of genetics, and to a smaller extent farm practices such as feed ration, in determining gMOS composition.